Um estudo do processo de desenvolvimento de cultivares por intermédio da Soft Systems Methodology em uma instituição de pesquisa agropecuária - Marcio Babosa Guimaraes Cota Junior (2008)
The objective of this essay is to use digital models predictors for rchelon of a supply chain of pharmacist products and cosmetics, mainly for FMX Company that represents the weak echelon of the chain.The methodology is based on control systems and allows us to gain valuable insights into the dynamic behavior of supply chain replenishment rules. Also introduce engineering control concepts to quantify the variance amplification bullwhip effect (Forrester Effect) or variance reduction and in consequence the decreasing inventoriesthroughout the chain, making it competitive. The applied methodology was the case study, within two echelons of the chain through real data and composed of up to and out order, it means, orders from an echelon down to and up to another one. At the end signaling demands were compared with and without filters, indifferent echelons, as well as the influence of the professional that is in charge of signaling the demand.